Ageing and mental health: changes in self-reported health due to physical illness and mental health status with consecutive cross-sectional analyses. Issue 1 (18th January 2017) - Lorem, Geir Fagerjord; Schirmer, Henrik; Wang, Catharina E A; Emaus, Nina
Abstract : Objectives: It is known that self-reported health (SRH) declines with increasing age and that comorbidity increases with age. We wished to examine how age transfers its effect to SRH through comorbid disease and mental illness and whether these processes remained stable from 1994 until 2008. The hypothesis is that ageing and/or the increased age-related burden of pathology explains the declining SRH. Setting: The Tromsø Study (TS) is a cohort study using a survey approach with repeated physical examinations. It was conducted in the municipality of Tromsø, Norway, from 1974 to 2008. Participants: A total of 21 199 women and 19 229 men participated. Primary and secondary outcome measures: SRH is the outcome of interest. We calculated and compared the effect sizes of age, comorbidity and mental health symptoms using multimediator analysis based on OLS regression. Results: Ageing had a negative impact on SRH, but the total effect of age decreased from 1994 to 2007. We assessed the direct effect of age and then the proportion of indirect age-related effects through physical illness and mental health symptoms on the total effect. The direct effect of age represented 79.3% of the total effect in 1994 and decreased to 58.8% in 2007. Physical illness emerged as an increasingly important factor and increased its influence from 15.7% to 41.2% of the total effect. Age alone had a protective effect on mental health symptoms and this increased (2.5% to 17.3%), but we found a stronger association between mental health symptoms and physical disease in the later waves of the study (increasing from 3.7% to 14.8%). Conclusions: The results suggest that the effect on SRH of mental health symptoms caused by physical illness is an increasing public health problem. Treatment and care for specific medical conditions must therefore focus more strongly on how these conditions affect the patient's mental health and address these concerns accordingly.